The Role of Motivation in Long-Term Second Language Retention: A Study of University Students in Khyber Pakhtunkhwa, Pakistan: https://doi.org/10.5281/zenodo.17444095 - Zahid Sardar; Qaisar Hayat Khattak (Journal of Religion and Society, 2025)
Motivation is still among the most critical influences that define success and sustainability in the acquisition of the second language. Although students can be capable of showing their level of proficiency when they are provided with formal instructions, their retention and usage of the language in the long run, is depended mostly on the intensity and influence of motivational mechanisms. This paper examines how intrinsic and extrinsic motivation can be used to facilitate a long-term retention of the English as a second language among university students in Khyber Pakhtunkhwa, Pakistan. The research behaviours is a mixed-method (questionnaires and semi-structured interviews) study that examines the effect of motivational variables on continuing the use of the English language following the formal instructional training. The results have shown that intrinsic motivation, which entails personal interest, enjoyment, and self-development, is more effective in maintaining language use, and extrinsic motivation, i.e., grades, employment, or social prestige tends to produce a short-lasting but more effective retention. The research findings are summarized that both types of motivation are to be encouraged in educational institutions, although the emphasis should be put on intrinsic motivation in order to increase the level of linguistic competence and retention among learners. Keywords: Second Language acquisition (SLA); Motivation; Intrinsic Motivation; Extrinsic Motivation; Language Retention; English Language Learning, University students; Khyber Pakhtunkhwa; Pakistan; Mixed-Method Research; Language Proficiency; Educational Psychology; Learner Engagement; Long-Term Retention; Language Pedagogy.